Cooperation in polygynous households - Barr, Abigail; Dekker, Marleen; Janssens, Wendy; Kebede, Bereket; Kramer, Berber (International Food Policy Research Institute, 2017)
Evidence that monogamous spouses often compromise household gains to maintain individual control over resources has informed the design of cash transfer schemes and other poverty alleviation programs. In polygynous households, decision making may be even less cooperative as co-wife conflict is common and welfare outcomes are often worse than in monogamous households, despite polygyny being associated with better ex ante prospects. Using a carefully designed series of two-person public goods games, we conduct a quantitative, ceteris paribus comparison of willingness to cooperate to maximize household gains across the two household types. We find that polygynous spouses and co-wives are less cooperative, one with another, than monogamous spouses. Co-wives are least cooperative toward each other and polygynous husbands are less cooperative with each of their wives than monogamous husbands are with their one wife. Finally, there are differences across the household types in the way husbands and wives condition their cooperativeness on how much they believe their spouses and co-wives will cooperate. Specifically, behavior in polygynous households is more reciprocal and apparently less altruistic than in monogamous households. This has implications for the design of poverty alleviation programs that transfer resources either in cash or in-kind.